Unraveling Mechanisms of Chiral Induction in Double-Helical Metallopolymers - Emrys Evans (Journal of the American Chemical Society, 2018)
Self-assembled helical polymers hold great promise as new functional materials, where helical handedness controls useful properties such as circularly polarized light emission or electron spin. The technique of subcomponent self-assembly can generate helical polymers from readily prepared monomers. Here we present three distinct strategies for chiral induction in double-helical metallopolymers prepared via subcomponent self-assembly: (1) employing an enantiopure monomer, (2) polymerization in a chiral solvent, (3) using an enantiopure initiating group. Kinetic and thermodynamic models were developed to describe the polymer growth mechanisms and quantify the strength of chiral induction, respectively. We found the degree of chiral induction to vary as a function of polymer length. Ordered, rod-like aggregates more than 70 nm long were also observed in the solid state. Our findings provide a basis to choose the most suitable method of chiral induction based on length, regiochemical, and stereochemical requirements, allowing stereochemical control to be established in easily accessible ways.